Efforts To Overcome the Digital Crime Modus Operandi of Clicking Whatsapp Links that Harm Customers Using the 4c Diamond Framework with Tows Analysis - Wijaya, Oki; Sunarno, AG; Sutono, S. (Manunggal Halim Jaya, 2025)
This research aims to determine efforts to overcome digital crime, the modus operandi of clicking WhatsApp links that harm customers using TOWS analysis at PT. Bank Rakyat Indonesia Kudus branch. The research sample consisted of 8 sources (informants) who were selected based on holding positions starting from Head of Unit as well as additional informants who were competent in their fields, Supervisor, 2 (two) CS and 2 (two) IT officers, who had sufficient time to be interviewed and were willing to become informants. Data was collected through interviews and analyzed qualitatively using the 4c diamond framework using TWOS analysis. The research results showed that efforts to overcome digital crime, the modus operandi of clicking WhatsApp links, was based on the 4c diamond perspective. Where category 4c includes Change, Competitor, Customer and Company. Based on the perspective of change (change), the following crime prevention efforts use Strength and Opportunities strategies. This is due to the tendency for opportunities to be compared to threats and for strengths to be compared to weaknesses, so it is not meaningful for the BRI Undaan Kudus Unit. As well as the Strategy position Based on TOWS Analysis at PT. Bank Rakyat Indonesia Undaan Unit. Based on the TOWS analysis results, the BRI Undaan Kudus Unit is in quadrant 1, where this quadrant indicates that the situation is very favorable for the BRI Undaan Kudus Unit.